Glycemic thresholds for diabetes-specific retinopathy: Implications for diagnostic criteria for diabetes - Colagiuri, S.; Lee, Crystal; Wong, T.; Balkau, B.; Shaw, J.; Borch-Johnsen, K. (American Diabetes Association, 2011)
OBJECTIVE :To re-evaluate the relationship between glycemia and diabetic retinopathy. RESEARCH DESIGN AND METHODS: We conducted a data-pooling analysis of nine studies from five countries with 44,623 participants aged 20-79 years with gradable retinal photographs. The relationship between diabetes-specific retinopathy (defined as moderate or more severe retinopathy) and three glycemic measures (fasting plasma glucose [FPG; n = 41,411], 2-h post oral glucose load plasma glucose [2-h PG; n=21,334], and A1C [n=28,010]) was examined. RESULTS: When diabetes-specific retinopathy was plotted against continuous glycemic measures, a curvilinear relationship was observed for FPG and A1C. Diabetes-specific retinopathy prevalence was low for FPG <6.0 mmol/l and A1C <6.0% but increased above these levels. Based on vigintile (20 groups with equal numbers) distributions, glycemic thresholds for diabetes-specific retinopathy were observed over the range of 6.4-6.8 mmol/l for FPG, 9.8 -10.6 mmol/l for 2-h PG, and 6.3-6.7% for A1C. Thresholds for diabetes-specific retinopathy from receiver-operating characteristic curve analyses were 6.6 mmol/l for FPG, 13.0 mmol/l for 2-h PG, and 6.4% for A1C. CONCLUSIONS: This study broadens the evidence based on diabetes diagnostic criteria. A narrow threshold range for diabetes-specific retinopathy was identified for FPG and A1C but not for 2-h PG. The combined analyses suggest that the current diabetes diagnostic level for FPG could be lowered to 6.5 mmol/l and that an A1C of 6.5% is a suitable alternative diagnostic criterion.